2021
DOI: 10.3389/fimmu.2021.744477
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1 Amplifies Ovalbumin-Induced Airway Remodeling by Strengthening TGFβ1/Smad3 Action

Abstract: Syndecan-1 (SDC-1) is a transmembrane proteoglycan of heparin sulfate that can regulate various cell signal transduction pathways in the airway epithelial cells and fibroblasts. Airway epithelial cells and human bronchial fibroblasts are crucial in airway remodeling. However, the importance of SDC-1 in the remodeling of asthmatic airways has not been confirmed yet. The present study was the first to uncover SDC-1 overexpression in the airways of humans and mice with chronic asthma. This study also validated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…SDC-1 also prevented hepatocellular carcinoma by interfering with several signaling pathways and enhancing cell-cycle blockade (41). In asthma, increased SDC-1 expression was correlated with TGFβ1/Smad3mediated airway remodeling in vivo and in vitro (42,43). We found that overexpression of miR-19a-3p inhibited the expression of SDC-1, TGF-β1 and p-Smad3 proteins in ox-LDL-induced HAECs.…”
Section: Discussionmentioning
confidence: 70%
“…SDC-1 also prevented hepatocellular carcinoma by interfering with several signaling pathways and enhancing cell-cycle blockade (41). In asthma, increased SDC-1 expression was correlated with TGFβ1/Smad3mediated airway remodeling in vivo and in vitro (42,43). We found that overexpression of miR-19a-3p inhibited the expression of SDC-1, TGF-β1 and p-Smad3 proteins in ox-LDL-induced HAECs.…”
Section: Discussionmentioning
confidence: 70%
“…In Stigmasterol + rh-NK1R group, cells were treated with 20 μg/mL stigmasterol and 1 μM (Zhang et al. 2021 ) recombinant human NK1R protein for 24 h.…”
Section: Methodsmentioning
confidence: 99%